FX interventions in Brazil: a synthetic control approach - Marcos Chamon; Marcio Garcia; Laura Souza (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2015)
The taper tantrum of May 2013 generated sharp fall in risky assets prices, including the depreciation of several emerging market currencies. To fight excess volatility and exchange rate overshooting, the Central Bank of Brazil announced a major program of interventions in foreign exchange markets. We use a synthetic control approach to determine whether or not the intervention program was successful. Our results suggest that the first FX intervention program mitigated the depreciation of the real against the dollar. A second announcement made later in the year that the program was going to continue on a smaller basis had a smaller effect, which was not significant. This result is corroborated by a standard event study methodology. We also document that both program did not have an impact on the volatility of the exchange rate.
Keywords: F31; G14; 330; FX interventions; synthetic control; ArCo